Using the swimbladder as a respiratory organ and/or a buoyancy structure—Benefits and consequences. Issue 9 (8th April 2021) - Pelster, Bernd
Abstract: A swimbladder is a special organ present in several orders of Actinopterygians. As a gas‐filled cavity it contributes to a reduction in overall density, but on descend from the water surface its contribution as a buoyancy device is very limited because the swimbladder is compressed by increasing hydrostatic pressure. It serves, however, as a very efficient organ for aerial gas exchange. To avoid the loss of oxygen to hypoxic water at the gills many air‐breathing fish show a reduced gill surface area. This, in turn, also reduces surface area available for other functions, so that breathing air is connected to a number of physiological adjustments with respect to ion homeostasis, acid–base regulation and nitrogen excretion. Using the swimbladder as a buoyancy structure resulted in the loss of its function as an air‐breathing organ and required the development of a gas secreting mechanism. This was achieved via the Root effect and a countercurrent arrangement of the blood supply to the swimbladder. In addition, a detachable air space with separated blood supply was necessary to allow the resorption of gas from the swimbladder. Gas secretion as well as gas resorption are slow phenomena, so that rapid changes in depth cannot instantaneously be compensated by appropriate volume changes. As gas‐filled cavities the respiratory swimbladder and the buoyancy device require surfactant. Due to high oxygen partial pressures inside the bladder air‐exposed tissues need an effective reactive oxygen species defense system, which is particularly important for a swimbladder at depth. Graphical abstract: HIGHLIGHTS: Using a swimbladder for aerial respiration severely affects homeostasis of various body functions Surfactant and a reactive oxygen species defense system are essential Rapid changes in hydrostatic pressure can hardly be compensated